Aportes a la flora polínica de turberas altoandinas, Provincia de Jujuy, noroeste argentino - Torres, Gonzalo R.; Schittek, Karsten (Gayana botanica, 2012)
The descriptions of 15 pollen types, new for the high-Andean pollen flora, distributed in 12 families, are presented, with a key for their identification. They belong to the current flora of cushion peatlands' plants communities. The aim of these studies is to contribute to the knowledge of pollen of high Andean peatland ecosystems, in order to optimize the identification of pollen types conserved in quaternary fossil records in Northwestern Argentina (NOA). The following species are described: Apiaceae: Lilaeopsis macloviana, Asteraceae: Cuatrecasasiella argentina, Perezia pygmaea, Brassicaceae: Eudema friesii, Cyperaceae: Carex gayana, Zameioscirpus muticus, Fabaceae: Astragalus micranthellus, Gentianaceae: Gentianella meyeniana, Juncaceae: Distichia muscoides, Orobanchaceae: Bartsia crenoloba, Castilleja pumila, Plantaginaceae: Plantago tubulosa, Poaceae: Puccinellia frigida, Portulacaceae: Calandrinia compacta, Ranunculaceae: Halerpestes exilis.